(untitled) - Griffin, Charles H. (Homewood, Illinois, 1980)
Offer your students the most authoritative, comprehensive coverage of advanced accounting topics available with Fischer/Taylor/Cheng's ADVANCED ACCOUNTING, Tenth Edition. Fully revised to incorporate the latest FASB statements and their impact on consolidations, ADVANCED ACCOUNTING, Tenth Edition, combines sound theoretical foundations with a hands-on, learn-by-example approach that has established this text as the prominent leader in today's advanced accounting classrooms. ADVANCED ACCOUNTING, Tenth Edition, closely links theory and practice, helping students visualize the application of theories through numerous actual examples common in today's accounting. The text's proven focus on conceptual understanding and clear presentation style make even the most complex topics approachable.
Keywords: Accounting